Genomic insight into COVID-19 severity in MAFLD patients: a single-center prospective cohort study - Buchynskyi, Mykhailo; Oksenych, Valentyn; Kamyshna, Iryna; Budarna, Olena; Halabitska, Iryna; Petakh, Pavlo; Kamyshnyi, Oleksandr (Frontiers in Genetics, 2024)
This study investigated the influence of single nucleotide polymorphisms (SNPs) in genes associated with the interferon pathway (IFNAR2 rs2236757), antiviral response (OAS1 rs10774671, OAS3 rs10735079), and viral entry (ACE2 rs2074192) on COVID-19 severity and their association with nonalcoholic fatty liver disease (MAFLD). We did not observe a significant association between the investigated SNPs and COVID-19 severity. While the IFNAR2 rs2236757 A allele was correlated with higher creatinine levels upon admission and the G allele was correlated with lower band neutrophils upon discharge, these findings require further investigation. The distribution of OAS gene polymorphisms (rs10774671 and rs10735079) did not differ between MAFLD patients and non-MAFLD patients. Our study population's distribution of ACE2 rs2074192 genotypes and alleles differed from that of the European reference population. Overall, our findings suggest that these specific SNPs may not be major contributors to COVID-19 severity in our patient population, highlighting the potential role of other genetic factors and environmental influences.